Warga TPA Cipayung Pegiat Zero Waste: Produksi Pembalut Kain Selamatkan Diri dan Lingkungan - Terry Y. R. Pristya; Rizki Amalia (Universitas Mathla'ul Anwar Banten, 2021)
CIPAYUNG LANDFILL CITIZEN AS ZERO WASTE ACTIVATOR: PRODUCTION OF MENSPAD FOR SAVE HERSELF AND ENVIRONMENT. The mountain of garbage at the Cipayung landfill was overload. The volume of disposable sanitary napkins which increases if not controlled, will be very dangerous for the environment of the landfill. In addition, if the behavior of residents who use disposable pads does not pay attention to vaginal hygiene, it will increase the health problems faced. The zero waste was hope to be able to reduce problems there. The study conducted on housewife in August 25th 2020 Cipayung Landfill Depok, West Java. We conducted activites provided workshop to make menspad with portable sewing machine and also manual sewing needle. And also using color flyer for media in the workshop. The result showed that all of participants can make the menspad well which is environmentally friendly and healthy for women. Furthermore this study was increased the productivity of housewive to re-create the menspad using unused cloth in their home.